PENERAPAN MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA KELAS IV DI SDN 160 INPRES LEMO-LEMO KAB. MAROS - yusmaniar; Afni, Nur; Alannasir, Wahyullah (Program Studi Pendidikan Sekolah Dasar Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Makassar, 2024)
This study aims to understand: (1) Description of the Application of the Problem Based Learning Model to Improve Critical Thinking Skills of Grade IV Students at SDN 160 Inpres Lemo-lemo Kab. Maros. (2) Problem Based Learning Model to Improve Critical Thinking Skills of Grade IV Students at SDN 160 Inpres Lemo-lemo Kab. Maros. The type of research used is classroom action research (PTK). The population and research sample were 23 students in grade IV at SDN 160 Inpres Lemo-lemo, Maros Regency. The research instruments were teacher and student observation sheets, multiple choice tests and essays and documentation. The data analysis used is qualitative data. The research results obtained are: (1) Application of the Problem Based Learning Model to Improve Critical Thinking Skills of Grade IV Students at SDN 160 Inpres Lemo-lemo Kab. Maros through cycle I and cycle II. (2) There is an increase in students' critical thinking skills through the application of the Problem Based Learning model with an average score of 56.3 at a percentage value of 17.3% referred to in the quite critical category in cycle I and an average score of 88.6 at a percentage value of 82.6% referred to in the critical category in cycle II. Based on the research, the Application of the Problem Based Learning Model to Improve the Critical Thinking Ability of Grade IV Students at SDN 160 Inpres Lemo-lemo Maros Regency has increased.